Peatland Management Based on Local Wisdom Through Rural Governance Improvement and Agroindustry - Muhammad Arif KAMAL; Medea R. UTOMO; M. Lukman HAKIM; Indah Dwi QURBANI; Abdi Dzil IKRAM (Indonesia Strategic Sustainability, 2023)
This paper aims to examine various types of local wisdom that are carried out in managing peatlands in a sustainable manner within the framework of community-managed areas (wilayah kelola rakyat). The concept consists of four components, there are Tata Kuasa (Governance), Tata Kelola (Management), Tata Produksi (Production) and Tata Konsumsi (Consumption) which will be used as a peatland management framework. The use of this concept is expected to be a guide in managing peatlands through improving village governance and implementing agroindustry on peatlands based on local wisdom. The research was conducted in 16 villages in two districts in Jambi Province, Tanjung Jabung Barat and Tanjung Jabung Timur. The methods used are field observations, interviews and literature studies related to local wisdom, village governance and agroindustry. The results obtained are that actually the village community is able to utilize and process natural potential with existing local wisdom and is able to implement it in the form of village governance through drafting village regulations and processing agricultural products as part of agroindustry.